Maqashid Syari'ah dalam Istinbath Hukum - Al'Ula, Moh. Firdaus Faiz; Kholik, Jamaludin Acmad (Al-Maslahah : Jurnal Ilmu Syariah, 2025)
Maqāshīd Shari'ah represents a significant component of ushul fiqh, functioning as a principal reference point for the formulation of Islamic legal principles. This article presents a discussion of the concept, division, and role of Maqashid Shari'ah in the process of istinbath law. The prioritization of benefit and avoidance of harm that characterizes maqāshīd leads to the identification of five main objectives: the protection of religion, the soul, the mind, the offspring, and property. The levels of Maqashid Shari'ah are classified into three categories: daruriyat (primary), hajiyat (secondary), and tahsiniyat (supplementary). These categories serve to prioritize needs in the context of legal conflicts. The process of Ijtihād is elucidated through the ta'lili and istislahi approaches, which facilitate the continued relevance of Islamic law in contemporary contexts. The article underscores the necessity for mujtahids to possess a profound comprehension of Maqashid Shari'ah in order to develop legal frameworks that are not only sharī'ah-compliant but also capable of addressing the demands of modern society. Through this analysis, the article posits that the maqashid approach renders Islamic law a malleable system that is adaptable to social changes.